The Effect of Digital Transformation on Governance in Indonesia: A Case Study of e-Government Implementation in Public Services - Elvira Fitriyanti (Politeknik Siber Cerdika Internasional, 2024)
The digital transformation of government, particularly through the implementation of e-Government, has brought significant changes to public service delivery, governance transparency, and administrative efficiency. This study investigates the impact of e-Government on governance practices in Indonesia, focusing on a case study of selected digital service implementations within public administration. Through a qualitative approach, data are gathered from government reports, public feedback, and expert interviews to evaluate the influence of digital innovation on service accessibility, accountability, and public satisfaction. Findings reveal that while e-Government has enhanced service efficiency and citizen engagement, challenges persist in terms of digital literacy, infrastructure, and interdepartmental integration. This research provides insight into the benefits and limitations of digital governance initiatives, offering recommendations for policymakers to optimize e-Government practices that align with the demands of an increasingly digital society.